METODE PEMBELAJARAN PERMAINAN BOLA TANGAN DENGAN MENGGUNAKAN LATIHAN LADDER DRILL HOP SCOTCH PENGARUHNYA TERHADAP KEMAMPUAN AGILITY BERMAIN BOLA TANGAN - Rohman, Ujang (Buana Pendidikan, 2018)
This research is motivated by the fact that teaching in activities Students of the 2015 Sports Coaching Education, the Teaching and Education Faculty of the University of PGRI Adi Buana Surabaya the delivery of training materials less than the maximum, so that learners become passive and processes running less interesting extracurricular activities. Agility on hand ball sport is a absolut needs wich is must be had by all of hand ball’s atletes. Formulation of the problem in this research is "Hand ball learning method using training ladder drill hop scotch effect on ability materials to play hand ball" The goal is to determine the presence or absence of ladder drill hopscotch training for agility on hand ball game on boy students 18th grade of student of 2015 Sports Coaching. Agility is ability of someone to move faster and turn the navigate with agile. Agility is a combine of speed, strength, balance, flexibility and coordination. In this study to measure the agility use the instrumen of research zig-zag run test.. Subjects in this study consisted of 15 boy students. The method used for this study is one group pretest-posttest design. Data collection techniques using the test. Results of the t test obtained by value t = 6,795 and while t table with significance level of α = 5% (0.05) 1.761. Thus t count > t table is 6,795 > 1.761. This means that by using ladder drill hopscotch training influence the agility of hand ball game.